Cutting edge: limited specialization of dendritic cell subsets for MHC class II-associated presentation of viral particles. - Keller, SA; Bauer, M; Manolova, V; Muntwiler, S; Saudan, P; Bachmann, M (2010)
Dendritic cells (DCs) are the most important APC. It was recently reported that there is a dichotomy for Ag presentation by DC subsets; exogenous Ags reach the MHC class I pathway, but not the MHC class II pathway, in CD8(+) DCs, whereas CD8(-) DCs only process Ags for the MHC class II pathway. In this study, we used virus-like particles (VLPs) to show that CD8(+) and CD8(-) DCs efficiently capture and process VLPs for presentation in association with MHC class II in vivo. In contrast, CD8(+) DCs, but not CD8(-) DCs, cross presented VLP-derived peptides. This pattern was changed in an FcgammaR-dependent fashion in the presence of VLP-specific Abs, because under those conditions both DC subsets failed to efficiently cross present. Thus, the presentation of viral particles to CD4(+) T cells is not restricted to distinct DC subsets, whereas the presentation of viral particles to CD8(+) T cells is limited to CD8(+) DCs.